Attracting "cutting-edge" skills through reserve component participation - Treverton, Gregory F.; Oaks, David M.; Scott, Lynn M.; Adams, Justin L.; Dalzell, Stephen; National Defense Research Institute (U.S.). Forces and Resources Policy Center; Rand Corporation; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 2003)
People with complex, hard-to-train skills, such as information technology specialists, linguists, or scientists, are difficult for the military services to attract and retain, especially because there may not be a constant need or career path for them in the military. This report examines five new ideas for attracting such people into the Reserve Component (RC): (1) a Civilian Skills Database; (2) an expanded Individual Ready Reserve program; (3) a tailored version of the Employer Support to Guard and Reserve program; (4) an RC-focused program modeled on the Army's Partnership for Youth Success (PaYS) program; and (5) a Critical University Talent Program. The authors discuss the five programs in detail and suggest ways in which they could be pilot-tested.
Framing the Challenge -- Innovations for Meeting Current and Future Skill Needs -- Cutting-Edge Policy Initiatives -- Testing the Agenda.
"National Defense Research Institute."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: Manpower -- United States; United States -- Armed Forces -- Occupational specialties; United States -- Armed Forces -- Recruiting, enlistment, etc; United States -- Armed Forces -- Reserves; United States -- Defense